Potassium Permanganate Solution-containing Polyethylene Nanocomposite Film Used as Color Indicator in Smart Packaging - Mojgan Mirzataheri (علوم و تکنولوژی پلیمر, 2017)
In recent years, different color indicators have been developed and utilized in smart packaging to better visualize the fruit shelf-life and its safety consumption date as well as to minimize the loss of agricultural products. In this study, a potassium permanganate solution-containing polyethylene nanocomposite film was prepared through melt mixing process as color indicator for smart packaging. Two kinds of silica nanoparticles of different surface hydrophobicity were incorporated in the LDPE films to study the effect of hydrophilicity of nanoparticles on the film barrier properties. The morphology and dispersion of nanoparticles were studied using SEM/EDX technique. The gas permeability, dynamic scanning calorimetry, melt flow index and mechanical properties were investigated to find an optimum formulation. The results of the oxygen barrier tests showed that the increase of nanoparticles loading in the polymer matrix increased the permeability up to 95% for the sample containing 5% hydrophilic silica. The hydrophilic nanosilica was well dispersed in the matrix and generated void channels which allowed to form a permeable polymer film. The presence of nanosilica did not alter the polymer crystallinity as well as the mechanical properties of the nanocomposite films. The melt flow index data showed that the silica/polyethylene nanocomposites could be produced with appropriate processability. The color indicator was then fabricated using potassium permanganate placed on a woven fabric. The whole colored fabric was then put within a sealed permeable polyethylene bag. The efficiency of the color indicator against ethylene gas has been measured for a duration of 10 days which is suitable in kiwi fruit packaging.